2016
DOI: 10.1155/2016/2897048
|View full text |Cite
|
Sign up to set email alerts
|

Lesion in Scalp and Skull as the First Manifestation of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common primary tumor of the liver and the fifth most common cancer in the world. The lungs, bone, and lymph nodes are frequent sites of metastasis of HCC. The purpose of the present study is show that metastases, although rare, must be among the differential diagnosis of skin lesions and that a diagnostic research based on these findings can be conducted. The authors report a rare case of metastatic hepatocellular injury to the scalp and skull treated by a radical sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Characteristic, although rare, locations of solitary cutaneous metastases are the scalp and the umbilicus [5]. Cutaneous metastases, although rare, must be among the differential diagnosis of skin lesions and that a diagnostic research based on these findings can be conducted [8].…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic, although rare, locations of solitary cutaneous metastases are the scalp and the umbilicus [5]. Cutaneous metastases, although rare, must be among the differential diagnosis of skin lesions and that a diagnostic research based on these findings can be conducted [8].…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, they may manifest as lesions in the scalp and skull. 12,13 The incidence rate is about 9 to 17%, based on various studies, although the exact incidence is thought to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…According to gender distribution of primary tumours, we obviously found that the 100% of patients with uterus cancer (8/ 8) 64,65,84 while in 24.8% (30/121) cases, the diagnosis was synchronous. 7,8,18,20,23,31,33,35,44,46,48,56,68,69,72,73,[76][77][78]81,84,87,93,95,96,99,102,110,111 The specific sites of primary tumours in each of these subgroups were reported in Table S1 (Supporting Information). Considering cases diagnosed after the primary tumour, they were mainly derived from breast and GI cancers (18/88 cases each); synchronous cases prevalently had a GI origin (10/30 cases), while cases diagnosed before the primary tumour were only three (one from GI, namely one thyroid and one lung cancer).…”
Section: Demographic and Epidemiologic Datamentioning
confidence: 99%
“…Regarding clinical appearance, AN was identified as a nodule, plaque and patch in 58% (69/119), 8,9,21,22,24,27,33,34,37-41,43,44,46,47,49- 2,6,7,11,[14][15][16][17][18][19][20]23,25,29,67,96 respectively; under the general term of a 'mass' in 16.8% (20/119) 28,32,35,42,45,48,58,59,71,73,80,81,83,87,95,106,110,111,114,117 and as an 'excoriated lesion' in 2.5% (3/119) of cases. 69,78,109 Specifically, breast cancer was mainly associated with patch lesions (9/20), followed by plaques and nodules (five and five out of 20, respectively).…”
Section: Demographic and Epidemiologic Datamentioning
confidence: 99%
See 1 more Smart Citation